Implementasi Model Pembelajaran PJBL Berbantuan Media Flashcard untuk Meningkatkan Minat dan Keaktifan Belajar Peserta Didik Kelas 4 di Sekolah Dasar - Siska Aprilia Wati; Cicilia Ika Rahayu Nita; Kholiq Kholiq; Siska Aprilia Wati; Cicilia Ika Rahayu Nita (Universitas Negeri Malang, 2023)
Abstract: Interest and learning activeness are needed and must exist in students during the learning process. Because with the interest and liveliness of learning can help to achieve learning goals. Interest and learning activeness in grade 4 students of SDN Sukorejo can be said to be lacking. Students still have no interest and learning activeness in themselves. In addition, the learning carried out by the teacher still uses the lecture method and has not used learning media. This study aims to increase interest and learning activeness by using the PJBL learning model assisted by flashcard media for 4th grade students of SDN Sukorejo. This research is a class action research conducted in collaboration with the class teacher which was carried out for 2 cycles with each cycle having 2 meetings. Based on the pre-cycle results, an assessment was obtained with a percentage of 25 percent learning interest and 12.5 percent learning activeness. After implementing cycle 1, an assessment was obtained with a percentage of 37.5 percent learning interest and 25 percent learning activeness. In cycle 2, an assessment was obtained with a percentage of interest and learning activeness of 75 percent. In cycle 2, it has met the expectations of increasing students' interest and learning activeness with more than 50 percent of the total number of students included in the category of good interest and active learning. This shows that the use of PJBL learning model assisted by flashcard media is able to increase the interest and learning activeness of 4th grade students of SDN Sukorejo Kediri. Abstrak: Minat dan keaktifan belajar sangat dibutuhkan dan harus ada pada diri peserta didik selama mengikuti proses pembelajaran. Sebab dengan adanya minat dan keaktifan belajar dapat membantu untuk mencapai tujuan pembelajaran. Minat dan keaktifan belajar pada peserta didik kelas 4 SDN Sukorejo dapat dikatakan kurang. Peserta didik masih belum ada minat dan keaktifan belajar pada diri mereka. Selain itu, pembelajaran yang dilaksanakan oleh guru masih menggunakan metode ceramah dan belum menggunakan media pembelajaran. Pada penelitian ini bertujuan untuk meningkatkan minat dan keaktifan belajar dengan menggunakan model pembelajaran PJBL berbantuan media flashcard pada peserta didik kelas 4 SDN Sukorejo. Penelitian ini merupakan penelitian tindakan kelas yang dilakukan secara kolaborasi dengan guru kelas yang pelaksanaannya selama 2 siklus dengan setiap siklus terdapat 2 pertemuan. Berdasarkan hasil pra siklus diperoleh penilaian dengan persentase minat belajar 25 persen dan keaktifan belajar 12,5 persen. Setelah dilaksanakan siklus 1, diperoleh penilaian dengan persentase minat belajar 37,5 persen dan keaktifan belajar 25 persen. Pada siklus 2, diperoleh penilaian dengan persentase minat dan keaktifan belajar sebesar 75 persen. Pada siklus 2 telah memenuhi harapan peningkatan minat dan keaktifan belajar peserta didik dengan lebih dari 50 persen dari jumlah peserta didik termasuk dalam kategori minat dan aktif belajar yang baik. Hal ini menunjukkan bahwa penggunaan model pembelajaran PJBL berbantuan media flashcard mampu meningkatkan minat dan keaktifan belajar peserta didik kelas 4 SDN Sukorejo Kediri.